2007
DOI: 10.1007/s10692-007-0007-x
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of viscose fibres with orthophosphoric acid and study of their physicochemical and mechanical properties

Abstract: Esterification of viscose fibres with aqueous solutions of orthophosphoric acid and urea at different ratios of components was investigated. It was shown that in phosphorylation of cellulose with these solutions, onesubstituted cellulose phosphates are formed and a side process of formation of cellulose carbamates takes place together with accumulation of phosphate groups. A decrease was found in the mechanical strength of the phosphorylated cellulose preparations and the degree was a function of the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…In fact, in addition to the high phosphate content, the length of the phosphorylated bers is the greatest and the level of nes is lower (Table 2). The quantication of the amount of graed phosphorus as a function of the amount of urea used clearly shows that a large proportion of the cellulosic bers have been phosphorylated with a high percentage compared to the previous works, which do not exceed 13% of P. [20][21][22]36,[42][43][44][45][46][47] Moreover, we carried out several tests by varying the concentration of phosphoric acid, considering the degradation effects of cellulosic chains, which can be generated by the release of acid at high temperatures. 3 It was found that the content of the P element in the phosphorylated samples (PKP1 and PKP4) decreased sharply from 14.87 to 11.05% in an acid concentration of 2 and 3 M, respectively.…”
Section: Elemental Analysis and Mapping Of Modied Cellulosic Bersmentioning
confidence: 91%
“…In fact, in addition to the high phosphate content, the length of the phosphorylated bers is the greatest and the level of nes is lower (Table 2). The quantication of the amount of graed phosphorus as a function of the amount of urea used clearly shows that a large proportion of the cellulosic bers have been phosphorylated with a high percentage compared to the previous works, which do not exceed 13% of P. [20][21][22]36,[42][43][44][45][46][47] Moreover, we carried out several tests by varying the concentration of phosphoric acid, considering the degradation effects of cellulosic chains, which can be generated by the release of acid at high temperatures. 3 It was found that the content of the P element in the phosphorylated samples (PKP1 and PKP4) decreased sharply from 14.87 to 11.05% in an acid concentration of 2 and 3 M, respectively.…”
Section: Elemental Analysis and Mapping Of Modied Cellulosic Bersmentioning
confidence: 91%
“…The increase in urea concentration had active impacts on the reaction in terms of enhancing charge when heat-treating for the same time (90 min). Similar studies have reported to increase charge of the phosphorylated cellulose fibers by increasing urea usage. , …”
Section: Resultsmentioning
confidence: 99%
“…However, the charge density of P-H80-25 showed no significant difference compared to that of P80-25, which probably indicates that a longer heat-treatment time (e.g., 90 min) would be required to sufficiently implement the active effects of urea. In addition to heat-driven fiber swelling in the presence of urea, urea can act as a catalyst to promote the reaction . Decomposition of urea in the curing stage with release of ammonia causes accumulation of ammonium phosphate in the reaction system, which is an active phosphorylating agent .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations